Smartphone-Based Thermal Imaging: A New Modality for Tissue Temperature Measurement in Hand and Upper Extremity Surgeries. (May 2018) - Cao, Jue; Currie, Kelly; Carry, Patrick; Maddox, Grady; Nino, Samantha; Ipaktchi, Kyros
Background: Smartphone-based thermal imaging (SBTI) allows noninvasive temperature measurements. Its validity compared with a conventional infrared probe temperature scanner (IPTS) has not been studied. This study compares temperature measurements between the 2 technologies on human participants.Methods: Bilateral index finger temperature measurements were obtained on 30 healthy participants using IPTS and SBTI devices. Dominant versus nondominant sides (side-to-side difference) and individual side measurements between the 2 methods were compared for repeatability (precision) and agreement.Results: A total of 23 female and 7 male participants were tested. Based on nonoverlapping confidence intervals (CIs), intraclass correlation coefficient of repeatability was higher for SBTI than for IPTS measurements in side-to-side differences: 0.97 (95% CI, 0.96-0.99) versus 0.89 (95% CI, 0.82-0.95). The SBTI method recorded higher side-to-side difference and individual side measurements: 0.56°C (limits of agreement [LOA], −1.09°C to 2.20°C) and 2.64°C (LOA, 0.96°C-4.32°C), respectively.Conclusions: In addition to higher precision, SBTI offers added benefits of instantaneous acquisition of the temperature map of the entire hand, allowing quick comparisons of the uninjured and injured fingers. SBTI measurements consistently yielded higher temperature readings in the side-to-side difference as well as individual measurements. This suggested that both devices are not interchangeable for absolute temperature comparisons but are interchangeable in monitoring the changes in temperatures. This study suggests the potential for SBTI devices to be used in the clinical settings and may be of special benefit in telemedicine.